Pemberdayaan Kelompok Ibu PKK Desa Bresela dalam Peningkatan Pengetahuan Gizi Seimbang untuk Pencegahan Stunting - Anak Agung Gede Budhitresna; Sri Ratna Dewi; Ayu Savitri Siskayani; Kartika Sari (JURNAL SEWAKA BHAKTI, 2022)
Stunting is a linear growth disorder caused by chronic nutrient intake malnutrition and or chronic or recurrent infectious diseases as indicated by a z-score for height for age (TB/U) less than -2 standard deviations (SD) based on World Health Organization standards (WHO). Stunting describes chronic undernutrition status during growth and development since early life. The prevalence of stunting in Gianyar Regency, Bali Province in 2013 was 40.99%. One of the 10 villages at the locus of stunting in Gianyar Regency is Bresela Village. The main factor causing stunting in Gianyar district based on data verification from the District Health Office. Gianyar, among others: smoking habits, personal hygiene in food preparation, level of adequacy of vitamin A, and availability of clean water. The problems that are often found are the lack of knowledge, attitudes, and behavior of the community regarding balanced nutrition and stunting in toddlers, therefore, together with partners, community empowerment is carried out through counseling about balanced nutrition as an effort to prevent stunting. Based on the pre and posttest evaluations, it was found that the knowledge of the PKM partners had increased from before and after the education had increased significantly (p value = 0.000).